Pengaruh Penilaian Kinerja Motivasi Dan Kompetensi Terhadap Kepuasan Kerja Pegawai Di KPP Pratama Jakarta Penjaringan - Syabani, Gani (JIAP (Jurnal Ilmu Administrasi Publik), 2024)
The assessment of employee performance at KPP Pratama Jakarta Penjaringan refers to the Regulation of the Director General of Taxes Number PER-6/PJ/2023 concerning the Ranking of Employee Performance within the Director General of Taxes, which is carried out using the ranking method. If this assessment is not carried out objectively, it can cause employee demotivation, which can result in suboptimal employee performance. This research aims to analyze the influence of performance appraisal, competency, and motivation on job satisfaction and employee performance. It uses a quantitative method, a census conducted on 113 people (100%) employees. The research instruments are questionnaires and observations. The data collection technique is G-Form. Inferential statistical analysis is used using the SmartPLS 3.2.9 application. The research results show that employees are aged 23-54 (average 34 years), and the majority have a diploma. The level of performance assessment, competency, motivation and job satisfaction is in the Medium category. The variables for assessing employee performance, competence and motivation have positive values and have a significant effect on job satisfaction. There is a significant influence between employee job satisfaction on employee performance at KPP Pratama Jakarta Penjaringan.